On the computation of the GCD of 2-D polynomials - Tzekis, Panagiotis; Karampetakis, Nicholas P.; Terzidis, Haralambos K. (Zielona Góra: Uniwersytet Zielonogórski)
The main contribution of this work is to provide an algorithm for the computation of the GCD of 2-D polynomials, based on DFT techniques. The whole theory is implemented via illustrative examples.
Keywords: greatest common divisor; discrete Fourier transform; two-variable polynomial